Growth of the Maize Primary Root at Low Water Potentials : I. Spatial Distribution of Expansive Growth - Sharp, Robert E. (1988)
Seedlings of maize (Zea mays L. cv WF9 × Mo 17) were grown in vermiculite at various water potentials. The primary root continued slow rates of elongation at water potentials which completely inhibited shoot growth. To gain an increased understanding of the root growth response, we examined the spatial distribution of growth at various water potentials. Time lapse photography of the growth of marked roots revealed that inhibition of root elongation at low water potentials was not explained by a proportional decrease in growth along the length of the growing zone. Instead, longitudinal growth was insensitive to water potentials as low as − 1.6 megapascal close to the root apex, but was inhibited increasingly in more basal locations such that the length of the growing zone decreased progressively as the water potential decreased. Cessation of longitudinal growth occurred in tissue of approximately the same age regardless of spatial location or water status, however. Roots growing at low water potentials were also thinner, and analysis revealed that radial growth rates were decreased throughout the elongation zone, resulting in greatly decreased rates of volume expansion.